2008
DOI: 10.1002/qj.358
|View full text |Cite
|
Sign up to set email alerts
|

Observational validation of the compensating mass flux through the shell around cumulus clouds

Abstract: ABSTRACT:The existence of a subsiding shell around cumulus clouds has been observed before in several aircraft measurement campaigns. Recent results from large-eddy simulations (LES) showed that the downward mass flux through the shell compensates for a significant fraction of the upward mass flux through the cloud. In this study, aeroplane measurements from the Rain In Cumulus over the Ocean (RICO) field campaign are used to verify the existence of this compensating mass flux. Just as in the LES results, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 22 publications
10
55
3
Order By: Relevance
“…The skewness is significantly higher for the day with fair-weather cumuli development (5 April) than for the cloud-free day (5 May) in agreement with the discussion given by Heus et al (2009) and Verzijlbergh et al (2009).…”
Section: Meteorological and Turbulence Characteristicssupporting
confidence: 88%
“…The skewness is significantly higher for the day with fair-weather cumuli development (5 April) than for the cloud-free day (5 May) in agreement with the discussion given by Heus et al (2009) and Verzijlbergh et al (2009).…”
Section: Meteorological and Turbulence Characteristicssupporting
confidence: 88%
“…The plume is positively skewed, also observed in the bottom graph of the cloud layer. The value of the skewness is about 3 times higher than in the dry CBL, which is due to the rare but very strong in-cloud updrafts in the cumulus layer (Heus et al, 2009). Nonetheless, looking at the height of the maximum concentration, we observe that it descends only very slowly, unlike we would expect from the analogy with the CBL.…”
Section: Velocity Statisticscontrasting
confidence: 63%
“…This configuration of the cloud layer results in a top-hat velocity distribution that is strongly skewed ( Fig. 1d; Heus et al, 2009). On the basis of this velocity distribution, one would expect dispersion characteristics similar to those in the CBL.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Heus et al (2009) showed that to obtain correct values for the in-cloud vertical mass flux in cumulus clouds, much finer resolutions are necessary than are commonly used in for instance intercomparison studies. When the correct spatial mass flux distribution is desired, DALES shows convergence at a horizontal resolution of 25 m (see Fig.…”
Section: Resolution Dependencies and Convergencymentioning
confidence: 99%